Fluid flow of various configurations in a rock-proppant-system. Issue 1 (1st January 2023) - Witte, L C; Backers, T
Abstract: A high rock mass permeability is essential for developing an enhanced geothermal system and commonly achieved through the fracture conductivity. Hydraulic stimulation of fractures in combination with the use of proppants can significantly increase and maintain rock mass permeability. To investigate and quantify the effect of proppants, which are so far not commonly used to enhance deep geothermal reservoirs, on the rock mass hydraulic conductivity we performed various sets of laboratory experiments. We performed long-term creep deformation tests on a stack of rock samples with simultaneous a) fluid flow and b) acidification and fluid flow, in both cases with and without a proppant-filled fracture between the stacked rock samples. A central borehole served as fluid inlet into the lower sample of the stack. Two more boreholes in the lower sample allowed fluid flow. Sample stacks were placed in a Hoek cell at elevated confining pressures to prevent fluid flow along the sidewalls of the cylindrical sample setup. We compared the axial deformation and injection pressures between the experimental setups. The laboratory tests are part of the ZoKrateS Project, which aims at showing the feasibility of enhancing fractured carbonate rock mass by proppant placement for geothermal applications.